Waging a Visual War on Poverty: President Lyndon B. Johnson in Appalachia - Katharina Fackler (Current Objectives of Postgraduate American Studies)
The article investigates how press photographs shaped poverty discourses in the historical context of the War on Poverty. Using a picture of President Lyndon B. Johnson and a presumably poor woman as a case study, it examines how iconographic elements and the visualized rhetorical pattern of the American jeremiad serve to situate the poor within dominant middle-class ideologies.